HEURISTIC PROCEDURE FOR MULTI-WORKDAY VEHICLE ROUTING PROBLEM WITH PRE-ASSIGNED WORKERS AND MANUAL UNLOADING - Rattanamanee, Tarit; Nanthavanij, Suebsak; Dumrongsiri, Aussadavut (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
This paper deals with the multi-workday vehicle routing problem (MW-VRP) where delivery workers are pre-assigned to vehicles. At customer locations, workers must manually unload goods from vehicles. For each worker, the daily accumulated physical workload depends on the number of customers served by the vehicle and load demands at those customers. The MW-VRP is intended to determine daily delivery routes for a given set of vehicles over the multi-workday delivery period such that the maximum average percent residual energy (PRE) among all workers is minimized. A heuristic procedure is developed to firstly determine delivery routes for vehicles. Next, a greedy exchange algorithm is used to decrease the maximum average PRE among workers and total travel distance of vehicles. The results from the given numerical example show that the heuristic procedure is able to generate the routing solution with the same maximum average PRE as that from the optimal solution, but with a slightly greater total travel distance (11.57%).